Proceedings of the 23rd International Conference on Parallel Architectures and Compilation 2014
DOI: 10.1145/2628071.2628092
|View full text |Cite
|
Sign up to set email alerts
|

OpenTuner

Abstract: Program autotuning has been shown to achieve better or more portable performance in a number of domains. However, autotuners themselves are rarely portable between projects, for a number of reasons: using a domain-informed search space representation is critical to achieving good results; search spaces can be intractably large and require advanced machine learning techniques; and the landscape of search spaces can vary greatly between different problems, sometimes requiring domain specific search techniques to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(50 citation statements)
references
References 28 publications
0
49
0
1
Order By: Relevance
“…Enumerative solvers often rely on factoring the search space, aggressive pruning and lattice search. Factoring has been very successful for programming by example [8,10,17], and lattice search has been used in synchronization of concurrent data structures [23] and autotuning [2]. However, both factoring and lattice search require significant domain knowledge, so they are unsuitable for a general purpose system like Sketch.…”
Section: Related Workmentioning
confidence: 99%
“…Enumerative solvers often rely on factoring the search space, aggressive pruning and lattice search. Factoring has been very successful for programming by example [8,10,17], and lattice search has been used in synchronization of concurrent data structures [23] and autotuning [2]. However, both factoring and lattice search require significant domain knowledge, so they are unsuitable for a general purpose system like Sketch.…”
Section: Related Workmentioning
confidence: 99%
“…However, the challenges outlined in section 1.1 do not apply to the Hexagon family (which has an LLVM compiler, a single address space and data caching). Ansel et al [2014] and Mullapudi et al [2016] have demonstrated that automatic scheduling is possible for Halide through heuristic searches or model-based analysis, respectively. These approaches can likely be applied to DSPs as well, which would further reduce development times and increase portability.…”
Section: Related Halide Workmentioning
confidence: 99%
“…While the native method is usually called in place of the Python function provided by the programmer, the established best practice is to also provide a pure-Python implementation of each DSL, so that if the programmer ventures outside the subset of Python supported by an embedded DSL or runs the application on a platform without SEJITS installed, the application still executes as legal Python (albeit orders of magnitude more slowly, which is often fine for exploratory work on small problem sizes). The SEJITS framework provides the facilities for managing JIT compilation, caching the generated code for future calls, interfacing with autotuners such as OpenTuner [2], and so on.…”
Section: Background: Sejitsmentioning
confidence: 99%
“…The SEJITS framework is tightly integrated with OpenTuner [2], which allows the programmer to define a tuning harness for each specializer. While several individual specializers are integrated with OpenTuner, extending autotuning to meta-specialization involves much more complex tuning spaces.…”
Section: Autotuningmentioning
confidence: 99%